Menyikapi Lebaran Di Era Covid 19 Dengan Mentaati Protokol Kesehatan Lebaran - Iin Patimah; Chelsi; Sri Yekti Widadi; Tantri Puspita; Tanti Suryawantie; Mega Aprilianti (LP4M STIKes Karsa Husada Garut, 2020)
Eid homecoming or the Indonesia people know as “mudik lebaran” is a tradition of Indonesian society that is usually carried out by city residents who migrate to their hometowns at certain moments such as Eid. The condition of COVID 19, which recently became a pandemic throughout the country, seems to be a dilemma for the community to carry out homecoming because the Indonesian government is currently prohibiting city residents from going home so that the spread of the COVID19 outbreak in various regions. However, not all residents followed the government's advice, some residents continued to go home. The community service program with the theme Responding to Eid in the Covid 19 Era By Obeying the Lebaran Health Protocol aims to provide knowledge on how Eid is carried out in this era of COVID 19. This method of implementing community service through 3 stages, namely: preparation, implementation and documentation. This community service activity was attended by 120 participants, both residents of arrowroot andoutside of arrowroot who planned to go home and also as residents who have relatives who will return home in the near future. The implementation of community service using the Zoom application implements Health protocols to prevent transmission of COVID 19.